1992
DOI: 10.1111/j.1945-5100.1992.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Maralinga, a metamorphosed carbonaceous chondrite found in Australia

Abstract: Abstract-The Maralinga meteorite was found near the village of Maralinga, South Australia (30 018'S, 131°16'E) in 1974, but was not recognized as a meteorite until 1989. One weathered individual was recovered with a total mass of 3.38 kg. The bulk composition and petrography of Maralinga indicate that it is a metamorphosed (petrographic type 4) carbonaceous chondrite with major similarities to the Vigarano-subtype. However, recent trace element data from the literature suggest that Maralinga should be included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
2
25
2
Order By: Relevance
“…Keller et al (1992) reported rust stains surrounding some magnetite aggregates in CK4-an Maralinga, but our observations indicate that sulfides are the primary source of oxidized iron. The rust stains around Maralinga magnetite may be due to decomposition of associated sulfide.…”
Section: Source Of Brown Stainingmentioning
confidence: 42%
“…Keller et al (1992) reported rust stains surrounding some magnetite aggregates in CK4-an Maralinga, but our observations indicate that sulfides are the primary source of oxidized iron. The rust stains around Maralinga magnetite may be due to decomposition of associated sulfide.…”
Section: Source Of Brown Stainingmentioning
confidence: 42%
“…All these features are common to most CK chondrites (e.g., Geiger and Bischoff, 1989;1995;Kallemeyn et al, 1991;Keller et al, 1992;Rubin, 1992;Nakamura et al, 1993;Noguchi, 1993). The thin sections of Kobe show a higher modal abundance of chondrules ( 32 vol%) than typical CK4 5 chondrites (10 15 vol%; Kallemeyn et al, 1991).…”
Section: Discussion Classificationmentioning
confidence: 99%
“…However, there are considerable differences in chondrule abundance among the reported CK chondrites. For example, the Maralinga CK4 chondrite has a much higher abundance of chondrules ( 50 vol%) (Keller et al, 1992). Thus, there may be some range in chondrule abundance in CK chondrites.…”
Section: Discussion Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Y-82191 (CK6) exhibits anomalously high REE abundances (about 3 times CI), which appears to be parallel the higher abundances of Ca, Sr, Ba and K and lower abundances of Mg and Fe. The Maralinga (CK4) chondrite is considered to be an anomalous CK due to the fact that it contains much more abundant chondrules and CAIs compared with other CK (Keller et al, 1992). As shown in Fig.…”
Section: Detailed Ree Patternsmentioning
confidence: 99%